339 Dupilumab 16-week efficacy and safety are robust and consistent in adults over 60 years of age with moderate-to-severe atopic dermatitis. (25th January 2023) - Silverberg, Jonathan I; Lynde, Charles W; Abuabara, Katrina; Patruno, Cataldo; De Benedetto, Anna; Khokhar, Faisal A; Marco, Ainara Rodriguez; Levit, Noah A
Abstract: Atopic dermatitis (AD) may be more common than previously thought in adults aged ≥60 years, a population underrepresented in clinical trials. Rigorous demonstration of efficacy and safety in older adults is clinically important due to distinct disease presentations in this group, age-related immune shifts, changes in drug metabolism and risks associated with a heightened burden of medical comorbidities and polypharmacy. Treatment options providing efficacy with acceptable safety profiles are of particular importance. Here, we report the efficacy and safety of dupilumab for the treatment of moderate-to-severe AD in patients aged ≥60 years. Data were pooled from four randomized, placebo-controlled dupilumab trials in patients with moderate-to-severe AD (LIBERTY AD SOLO 1 & 2 [NCT02277743, NCT02277769], LIBERTY AD CAFÉ [NCT02755649] and LIBERTY AD CHRONOS [NCT02260986]). Patients aged ≥60 years ( N = 183) received dupilumab 300 mg weekly (qw), every 2 weeks (q2w) or a placebo. Topical corticosteroids (TCSs) were permitted in LIBERTY AD CAFÉ and LIBERTY AD CHRONOS. Reported efficacy measures include the percentage of patients achieving a 75% reduction in Eczema Area and Severity Index (EASI-75), mean change in Peak Pruritus Numerical Rating Scale (PP-NRS) scores, and mean change in Dermatology Life Quality Index (DLQI). Safety data are also presented. Among patients aged ≥60 years, significant increases in EASI-75 responses were observed in patients treated with dupilumab 300 mg qw (61.6%) and 300 mg q2w (63.0%) vs. placebo (14.3%; P < 0.0001 for both) at week 16. Least squares (LS) mean change (± standard error [SE]) in PP-NRS scores was significantly greater in patients treated with dupilumab 300 mg qw (−1.6 [0.2]) and 300 mg q2w (−1.7 [0.3]) vs. placebo (−0.9 [0.3]; P < 0.05 for both) at week 2. Improvements continued to week 16 in patients treated with dupilumab 300 mg qw (−4.0 [0.3]) and 300 mg q2w (−3.8 [0.3]) vs. placebo (−1.7 [0.3]; P < 0.0001 for both). Similarly, significant improvement (LS mean change [±SE]) in DLQI was seen in patients treated with dupilumab 300 mg qw (−5.0 [0.6]) and 300 mg q2w (−6.0 [0.7]) vs. placebo (−2.8 [0.6]; P < 0.01 vs. qw and P < 0.001 vs. q2w) at week 2; improvements continued to week 16 in patients treated with dupilumab 300 mg qw (−8.0 [0.6]) and 300 mg q2w (−9.65 [0.7]) vs. placebo (−3.3 [0.7]; P < 0.0001 for both). 52 (72.2%) patients in the 300 mg qw treatment group, 32 (58.2%) patients in the 300 mg q2w treatment group, and 40 (71.4%) patients in the placebo group experienced ≥1 TEAE. The two most common treatment-emergent adverse events (TEAEs) were injection-site reactions (13.9%) and nasopharyngitis (9.7%) during 300 mg qw dupilumab treatment; dermatitis atopic (20.0%) and nasopharyngitis (5.5%) during 300 mg q2w dupilumab treatment; and dermatitis atopic (30.4%) and upper respiratory tract infection (7.1%) during placebo treatment. 3 (4.2%) patients during 300 mg qw dupilumab treatment and 2 (3.6%) patients during 300 mg q2w dupilumab treatment discontinued treatment permanently as a result of TEAEs. Dupilumab efficacy and safety profiles in patients aged ≥60 years were generally consistent with that seen in patients aged <60 years with atopic dermatitis, and have been previously reported. Dupilumab, with or without TCS, improves AD signs, symptoms and quality of life with a consistent and acceptable safety profile in patients aged ≥60 years with moderate-to-severe AD.